IMPACT OF PLANT-BASED DIETARY FAT LEVELS ON GROWTH, FEED UTILIZATION, BODY COMPOSITION, AND SERUM METABOLITES IN LABEO ROHITA - Amara Akhtar, Ayesha Yaseen, Khadija Bareera, Saira Kanwal, Maniha, Umme Habiba, Muhammad Ahmed Saqib (Chelonian Research Foundation, 2024)
Fish is the preferred and the cheapest source of high-quality animal protein for humans. The study aimed to assess the influence of varying levels of plant dietary fats on the growth, feed utilization, body composition, and serum metabolites of Labeo rohita, a significant carp species known for its rapid growth and palatable flesh. Seventeen fingerlings were acclimatized and subjected to six different dietary treatments, including mono- and polyunsaturated fat supplements at 3%, 6%, and 9%. Serum metabolites were analyzed using the Biuret assay for total serum proteins, glucose peroxidase method for total serum glucose, cholesterol oxidase-phenol amino phenazone method for total serum cholesterol, and GPO/PAP method for serum triglycerides. Physiochemical parameters were meticulously maintained throughout the trial period. The results revealed that fish fed with 6% polyunsaturated and 9% monounsaturated fat exhibited significantly higher feed utilization and maximum growth performance, particularly in treatments 3 and 5. Furthermore, significant alterations in body composition and serum metabolites, such as proteins, triglycerides, and cholesterol, were observed in these treatments. The study concluded that 6% polyunsaturated fats (soybean + sunflower oil) and 9% monounsaturated fats (canola + olive oil) could effectively enhance the growth of Labeo rohita. Statistical analysis was executed using analysis of variance (ANOVA) and under central registration depositary (CRD). These findings offer valuable insights into optimizing the dietary requirements for the growth and health of Labeo rohita.